α7 Nicotinic Acetylcholine Receptor (α7nAChR) Expression in Bone Marrow-Derived Non-T Cells Is Required for the Inflammatory Reflex - Peder S. Olofsson; David A. Katz; Mauricio Rosas‐Ballina; Yaakov A. Levine; Mahendar Ochani; Sergio Iván Valdés‐Ferrer; Valentin A. Pavlov; Kevin J. Tracey; Sangeeta S. Chavan (2011)
The immune response to infection or injury coordinates host defense and tissue repair, but also has the capacity to damage host tissues. Recent advances in understanding protective mechanisms have found neural circuits that suppress release of damaging cytokines. Stimulation of the vagus nerve protects from excessive cytokine production and ameliorates experimental inflammatory disease. This mechanism, the inflammatory reflex, requires the α7 nicotinic acetylcholine receptor (α7nAChR), a ligand-gated ion channel expressed on macrophages, lymphocytes, neurons and other cells. To investigate cell-specific function of α7nAChR in the inflammatory reflex, we created chimeric mice by cross-transferring bone marrow between wild-type (WT) and α7nAChR-deficient mice. Deficiency of α7nAChR in bone marrow-derived cells significantly impaired vagus nerve-mediated regulation of tumor necrosis factor (TNF), whereas α7nAChR deficiency in neurons and other cells had no significant effect. In agreement with recent work, the inflammatory reflex was not functional in nude mice, because functional T cells are required for the integrity of the pathway. To investigate the role of T-cell α7nAChR, we adoptively transferred α7nAChR-deficient or WT T cells to nude mice. Transfer of WT and α7nAChR-deficient T cells restored function, indicating that α7nAChR expression on T cells is not necessary for this pathway. Together, these results indicate that α7nAChR expression in bone marrow-derived non-T cells is required for the integrity of the inflammatory reflex.